The Role of Poverty and Women's Human Capital on Regional Economic Growth in Indonesia: a Panel Data Analysis and Its Implications for Guidance and Counseling - Mira Miranda; Resti Susanti; Fauzi Nur Ilahi (Papanda Publisher, 2026)
This study examines the influence of women's human capital on regional economic growth in Indonesia and explores its implications for guidance and counseling practices. Specifically, the research analyzes the effect of female higher education participation, female labor force participation, poverty, and access to basic services on economic growth. The study employs a quantitative approach using panel data regression with observations from 34 provinces in Indonesia during the period 2018–2024. Due to data availability limitations, the dataset forms an unbalanced panel consisting of 135 observations. The estimation results using the Fixed Effect Model show that poverty has a significant negative effect on economic growth. Meanwhile, female higher education participation, female labor force participation, and access to basic services do not show a statistically significant effect during the observation period. These findings indicate that poverty remains a major structural barrier to regional economic growth, overshadowing the potential impact of women's human capital in the short term. The study highlights important implications for guidance and counseling services, particularly in supporting students from disadvantaged socioeconomic backgrounds. Counselors play a strategic role in providing career guidance, motivation, and educational planning to help break the intergenerational cycle of poverty and improve human capital quality.